The Ibero-Armorican arc: indentation versus self-subduction - Dias, Rui (2015)
In the Iberian Variscides it is possible to distinguish major arcuate structures; although highly studied, their characterization and genesis are still a matter of controversy. The main Ibero- Armorican Arc (IAA) is essentially defined by a NW–SE trend in the Iberian branch and an E–W trend in the Brittany branch; however, in northern Spain it is rotated 180º, sometimes known as the Cantabrian Arc (CA). The relationship between these arcs is debatable, being considered either as a single arc generated in one tectonic event, or the result of polyphase bending process. According to the last assumption, there is a later arcuate structure (CA), overlapping a previous major one (IAA). Whatever the proposed models, they must explain the presence of a sinistral transpression regime in Iberia and a dextral one in Armorican branch, and the temporal deformation range of Devonian to Upper Carboniferous (Dias and Ribeiro, 1995).